Human gamma-glutamyl hydrolase: cloning and characterization of the enzyme expressed in vitro. - Yao, R (1996)
A cDNA encoding human gamma-glutamyl hydrolase has been identified by searching an expressed sequence tag data base and using rat gamma-glutamyl hydrolase cDNA as the query sequence. The cDNA encodes a 318-amino acid protein of Mr 35,960. The deduced amino acid sequence of human gamma-glutamyl hydrolase shows 67% identity to that of rat gamma-glutamyl hydrolase. In both rat and human the 24 amino acids preceding the N terminus constitute a structural motif that is analogous to a leader or signal sequence. There are four consensus asparagine glycosylation sites in the human sequence, with three of them conserved in the rat enzyme. Expression of both the human and rat cDNA in Escherichia coli produced antigenically related proteins with enzyme activities characteristic of the native human and rat enzymes, respectively, when methotrexate di- or pentaglutamate were used as substrates. With the latter substrate the rat enzyme cleaved the innermost gamma-glutamyl linkage resulting in the sole production of methotrexate as the pteroyl containing product. The human enzyme differed in that it produced methotrexate tetraglutamate initially, followed by the triglutamate, and then the diglutamate and methotrexate. Hence the rat enzyme is an endopeptidase with methotrexate pentaglutamate as substrate, whereas the human enzyme exhibits exopeptidase activity. Another difference is that the expressed rat enzyme is equally active on methotrexate di- and pentaglutamate whereas the human enzyme has severalfold greater activity on methotrexate pentaglutamate compared with the diglutamate. These properties are consistent with the enzymes derived from human and rat sources.